Exploring the synergistic effect of feeding rates and feeding frequency on the population growth of brachionus plicatilis - Rizal Ismail; Sitti Raehanah Muhamad Shaleh; Norfazreena Mohd Faudzi; Faihanna Ching Abdullah; Najamuddin Abdul Basri; Teo, Kenneth Tze Kin (Egyptian Society for the Development of Fisheries Research & Human Health (ESDFRHH), Cairo, Egypt, 2025)
Rotifers play a crucial role in the aquaculture industry, particularly in the early stages of marine fish and crustacean larval rearing. This study aimed to identify the optimal feeding rates and frequencies for rotifers (Brachionus plicatilis), which are essential live feed in aquaculture. B. plicatilis (L- strain, mean lorica length 195.5 μm) was used in this experiment. The experiment consisted of 9 different combination treatments of feeding rates and feeding frequencies. 4- liter plastic jars were used for a 5-day experiment. An automated feeder was used to regulate the feeding rates and frequencies. Water temperature was set at 30℃ using aquarium heaters. Commercial concentrated Nannochloropsis sp. was used as feed throughout the experiment. The highest rotifer density, 378±12 rotifers/mL, was observed with a feeding rate of 200,000 cells/rotifer and a feeding frequency of 6 times per day (GR=1.18±0.006 day⁻¹). This was followed by a rotifer density of 292±9.54 rotifers/mL at a feeding rate of 100,000 cells/rotifer and the same feeding frequency (GR=1.13±0.007 day⁻¹). In contrast, the lowest density, 129±4.73 rotifers/mL, occurred with a feeding rate of 200,000 cells/rotifer and a feeding frequency of 2 times per day (GR=0.96±0.008 day⁻¹). The highest egg percentage (EP), 32.24±1.43%, was observed with a feeding rate of 200,000 cells/mL and a feeding frequency of 6 times per day, compared to the other treatments. It is deduced that both feeding rate and frequency have a significant effect on the population growth and the production of rotifers for aquaculture.